Effects of an 8-week intermittent aerobic training program on aerobic power in a professional soccer team - Miranda, G.; Aliberti, S.; Invernizzi, P. L. (Journal of Human Sport & Exercise, 2021)
Introduction Soccer is a very dynamic sport in which players must constantly adapt to game situations. As a result, the tension and effort during the game changes, depending on the action on the field. For this reason, aerobic power is a key element for a soccer player. Scope The objective is to test whether an 8-week intermittent training protocol can improve aerobic power in a professional soccer team. Methods The sample consisted of eighteen youth soccer players from a professional team with an average age of 17 years. For eight weeks, the players were subjected to intermittent training, i.e., running with variations in speed at predetermined times and distances: we proceeded with the principle of variation and progression of the load, up to week five, after which the intermittent work sessions were reduced to one per week. The reference parameter taken into consideration is the distance covered by the yo-yo intermittent recovery test, carried out before and after the training period. The Student's t-test for paired dependent samples was used as a statistical tool to verify the significance of the difference between the mean of the two tests. Results The result was statistically significant (p < .05). Intermittent training was able to improve aerobic power in professional soccer team. Conclusion From the data obtained it is possible to evaluate the characteristics of the players to propose personalized loads or organize the work in small groups as homogeneous as possible to make the training more effective.